1988
DOI: 10.1254/jjp.47.330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ammonia on the gastric mucosa in rats: Pathophysiological importance of urease in gastric ulcer disease.

Abstract: Abstract-We examined the pathophysiological roles of the urea-urease-ammonia system in gastric ulcer disease using rats. Exposure of the stomach to ammonia (0.01-1.0%) decreased the transmucosal potential difference (PD) and histological injury in a concentration-dependent manner.Exposure of the stomach for 20 min to urea (0.025-0.2%) together with urease (100 IU) produced a decrease in PD and microscopic injury similarly, and the lesion was closely associated with the amount of ammonia produced.Urea and ureas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…33 The increase in serum pepsinogen I was particularly marked in the renal failure patients with H pylon, with its concentration being double that in the renal patients without the infection. It has previously been reported that H pylon infection raises serum pepsinogen I in non-uraemic patients but only by about 25%.7 3 The fact that H pylon infection raises serum pepsinogen I to a greater extent in uraemic than non-uraemic subjects would be consistent with bacterial ammonia production raising the serum concentration of the zymogen. However, little is known about the mechanism by which pepsinogen I reaches the serum or about the mechanism of its renal excretion.33 If it is excreted by a saturable process then in patients with renal failure the same degree of increased delivery of pepsinogen I into the serum could produce a more marked increase in its serum concentration.…”
Section: Discussionmentioning
confidence: 80%
“…33 The increase in serum pepsinogen I was particularly marked in the renal failure patients with H pylon, with its concentration being double that in the renal patients without the infection. It has previously been reported that H pylon infection raises serum pepsinogen I in non-uraemic patients but only by about 25%.7 3 The fact that H pylon infection raises serum pepsinogen I to a greater extent in uraemic than non-uraemic subjects would be consistent with bacterial ammonia production raising the serum concentration of the zymogen. However, little is known about the mechanism by which pepsinogen I reaches the serum or about the mechanism of its renal excretion.33 If it is excreted by a saturable process then in patients with renal failure the same degree of increased delivery of pepsinogen I into the serum could produce a more marked increase in its serum concentration.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, the role of ammonia in H. pv/or/'-related gas tric mucosal damage has been widely recognized, and its toxic effect on normal gastroduodenal mucosa is well doc umented [10,11,[13][14][15][16][17], Nevertheless, most previous studies revealed the influences of ammonia only on the epithelium or gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely accepted that Helicobacter pylori is related to gastroduodenal diseases [8][9][10][11][12], The effect of ammonia, which is produced by the urease activity of H. pylori, on normal gastric mucosa has been well docu mented [13][14][15][16][17], Although a few papers refer to the effects of ammonia on gastric ulcer healing, those on the collagen metabolism in the ulcer base remain totally unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia is produced by the urease of Helicobacter pylori in the gastric mucosa, and it is considered to be one of the pathogens for H. pylori-induced gastric mucosal injury. NH 3 -AGML was first described by Murakami et al (1988a). It was reported to be inhibited by antioxidative agents (Murakami et al, 1989) and not by prostaglandins (PGs) (Murakami et al, 1988b).…”
Section: Antisecretory and Antiulcer Effects Of Cs-526 315mentioning
confidence: 99%